Kinetika dan Mekanisme Pelindian Limonit : Pengaruh Waktu dan Temperatur [Kinetics and Mechanism of Limonite Nickel Ore Dissolution : Effect of Time and Temperature] - Febriana, Eni; Tristiyan, Agung; Mayangsari, Wahyu; Prasetyo, Agus Budi (Jurnal Metalurgi, 2018)
Leaching by using sulfuric acid for nickel extraction of Halmahera limonite ore was investigated. Characterization of the ore was conducted by XRD (x-ray diffraction), XRF (x-ray flourescence), and SEM (scanning electron microscopy). The leaching was carried out under atmospheric pressure. Kinetic of leaching was studied by following the shrinking core model. The effect of temperatur and time were studied at various temperatures of 30, 50, and 90 °C with leaching time up to 480 minutes. A maximum 95% Ni extraction value was obtained for 480 min leaching at 90 °C from -150+200 mesh of limonitic nickel ore, with a concentration of H2SO4 of 1 M and a 2.5% ore / liquid ratio. The results show that the leaching rate of Ni is generally controlled by diffusion through the product layer with activation energy for the leaching of 78.0 kJ/mol. The leaching mechanism of limonite ores was identified from the result of residual leaching XRD graph. With increasing temperatur and the longer of leaching time, % extraction of Ni was increased. This condition followed by increasing of the quartz peak’s intensity at 2 = 26 °.